2016
DOI: 10.1002/cbic.201600306
|View full text |Cite
|
Sign up to set email alerts
|

Initial Molecular Recognition Steps of McjA Precursor during Microcin J25 Lasso Peptide Maturation

Abstract: Microcin J25 (MccJ25) has emerged as an excellent model to understand the maturation of ribosomal precursor peptides into the entangled lasso fold. MccJ25 biosynthesis relies on the post-translational modification of the precursor McjA by the ATP-dependent protease McjB and the lactam synthetase McjC. Here, using NMR spectroscopy, we showed that McjA is an intrinsically disordered protein without detectable conformational preference, which emphasizes the active role of the maturation machinery on the three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Recently, several groups have reported the in vitro mutagenesis of lasso peptides (Yan et al, 2012;Burkhart et al, 2015;Assrir et al, 2016;Zhu et al, 2016a;Cheung et al, 2016;DiCaprio et al, 2019;Koos and Link, 2019;Si et al, 2021). In a foundational study, the biosynthesis of MccJ25 was reconstituted in vitro by incubating the precursor peptide McjA with processing enzymes McjB and McjC in the presence of ATP and Mg 2+ (Yan et al, 2012).…”
Section: Other Potential Tailoring Enzymes For Engineering Lasso Peptides and The Chemoenzymatic Synthesis Of Lasso Peptidesmentioning
confidence: 99%
“…Recently, several groups have reported the in vitro mutagenesis of lasso peptides (Yan et al, 2012;Burkhart et al, 2015;Assrir et al, 2016;Zhu et al, 2016a;Cheung et al, 2016;DiCaprio et al, 2019;Koos and Link, 2019;Si et al, 2021). In a foundational study, the biosynthesis of MccJ25 was reconstituted in vitro by incubating the precursor peptide McjA with processing enzymes McjB and McjC in the presence of ATP and Mg 2+ (Yan et al, 2012).…”
Section: Other Potential Tailoring Enzymes For Engineering Lasso Peptides and The Chemoenzymatic Synthesis Of Lasso Peptidesmentioning
confidence: 99%
“…DUF553 (PF04473) proteins catalyze post-translational modifications of proteins by transferring, for example, peptidyl glutamine residues to a variety of amines ( 117 ). C96 family (Transglut_core3, PF13471) includes Escherichia coli McjB, which proteolytically processes McjA into a mature antimicrobial factor ( 118 ).…”
Section: Resultsmentioning
confidence: 99%
“…Worth noting is that a previous NMR study showed that both McjB and McjC bind to the N-terminus of the leader sequence and that McjC interacts predominantly with the V6-S18 region of the McjA core sequence. 144 Since this region largely defines the β-hairpin structure in MccJ25, it was proposed that McjC binding to the peptide may facilitate the pre-folding process. These data hint at the important roles of the C protein in substrate–protein interactions that remain to be discovered.…”
Section: The Biosynthesis Of Mccj25mentioning
confidence: 99%